Influence of Fortifying Graded Levels of Moringa oleifera Leaf Powder on Growth Performance and Haematobiochemical Indices of Broiler Chickens - Verma, Ajeet K.; Pramanik, Partha S.; Verma, Manoj K.; Gautam, Sachin; Kumar, Rajesh; Saurabh (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted to evaluate the influence of Moringa oleifera leaf powder (MOLP) on the growth and haemato-biochemical indices of broiler chickens. A total of 250-day-old broiler chicks (Vencobb-430) were randomly distributed into five groups with 5 replicates of 10 birds in each. Different dietary treatments were; basal diet with no supplement (NC- negative control) and a basal diet supplemented with antibiotics (PC-positive control), 1% MOLP (MOLP1), 1.5% MOLP (MOLP1.5), and 2% MOLP (MOLP2). Bodyweight gain (BWG), feed intake (FI), feed conversion ratio (FCR), haemato-biochemical parameters, and economics were assessed in 35 days of the experiment. The results showed that BWG of birds was significantly (p <0.05) higher in all Moringa supplement groups than NC group, but similar to PC group birds. Feed intake and FCR of Moringa supplemented and PC groups were significantly (p <0.05) lower than the NC group, except MOLP2, which showed no difference in FI compared with the NC group. MOLP1.5 group birds recorded the best value of FCR among different groups. The highest profit per broiler was recorded in MOLP1.5 followed by MOLP1 and MOLP2 than NC, similar to the PC group. Hb and PCV values of the MOLP1.5 group were significantly (p <0.05) higher than the NC group but comparable to the PC group. Platelet and WBC count were significantly (p <0.05) lower in Moringa supplemented groups than NC and PC groups. A significant (p <0.05) reduction was observed in blood glucose, SGPT, SGOT, cholesterol, and triglyceride levels of Moringa supplemented groups as compared to broilers of PC and NC groups. From the results, it was concluded that supplementation of 1.5% Moringa oleifera leaf powder improved the performance of birds without any detrimental effect on their health.